Degradation of Zr-based bulk metallic glasses used in load-bearing implants: A tribocorrosion appraisal. (July 2016) - Zhao, Guo-Hua; Aune, Ragnhild E.; Mao, Huahai; Espallargas, Nuria
Abstract: Owing to the amorphous structure, Bulk Metallic Glasses (BMGs) have been demonstrating attractive properties for potential biomedical applications. In the present work, the degradation mechanisms of Zr-based BMGs with nominal compositions Zr55 Cu30 Ni5 Al10 and Zr65 Cu18 Ni7 Al10 as potential load-bearing implant material were investigated in a tribocorrosion environment. The composition-dependent micro-mechanical and tribological properties of the two BMGs were evaluated prior to the tribocorrosion tests. The sample Zr65-BMG with a higher Zr content exhibited increased plasticity but relatively reduced wear resistance during the ball-on-disc tests. Both BMGs experienced abrasive wear after the dry wear test under the load of 2 N. The cross-sectional subsurface structure of the wear track was examined by Focused Ion Beam (FIB). The electrochemical properties of the BMGs in simulated body fluid were evaluated by means of potentiodynamic polarization and X-ray Photoelectron Spectroscopy (XPS). The spontaneous passivation of Zr-based BMGs in Phosphate Buffer Saline solution was mainly attributed to the highly concentrated zirconium cation (Zr 4+ ) in the passive film. The tribocorrosion performance of the BMGs was investigated using a reciprocating tribometer equipped with an electrochemical cell. The more passive nature of the Zr65-BMG had consequently a negative influence on its tribocorrosion resistance, which induced the wear-accelerated corrosion and eventually speeded-up the degradation process. It has been revealed the galvanic coupling was established between the depassivated wear track and the surrounding passive area, which is the main degradation mechanism for the passive Zr65-BMG subjected to the tribocorrosion environment.